PENGARUH KEKUASAAN DAN DESAIN ORGANISASI TERHADAP PERILAKU MANAJER: STUDI PADA PERUSAHAAN DAERAH AIR MINUM SE-PROVINSI KALIMANTAN SELATAN - Chairina Chairina (Journal of Indonesian Economy and Business (JIEB), 2007)
The purpose of this study is to examine relationship between formal authority structures, information characteristic, the open system culture, the tight control culture and informal authority structures with cost consciousness either through directly or indirectly on the use of Accounting Information System (AIS) for decision control and decision management. These topics are rarely examined specially behavior of cost consciousness. The result of this research contributes for theory development, particularly for behavioral accounting besaide, contribute to managerial practices in improving expense efficiency through behavior of cost consciousness.The Data of this study were taken from local government (watter supply) from kota and kabupaten in South Kalimantan. The questionnaire were distributed to middle manager and lower manager. The data were collected by mail survey and contact person. There were 400 questionnaires sent to respondent with 32.5 percent of respon rate. Analysis was conducted by using Two Step Approach to SEM tehnique with Lisrel 8.54 and SPSS version 11.The Result shows that formal authority structures does not related to accounting information system (AIS) for decision control and decision management. Information characteristic correlated positively by AIS to decision control but it does not related with decision management. The open system culture does not related to AIS for decision control and decision management. While tight control culture correlated posifively to AIS for decision control but it does not related with decision management. Informal authority structures does not related to AIS for decision control and decision management. Decision control and decision management correlated positively with cost cosnsciousness. Formal authority structure corretaled directly with cost consciousness, while informal authority structure does not correlated directly with cost consciousness.